Réponses

  • Utilisateur Brainly
2013-06-18T17:29:41+02:00

a) 3( x+6) =3x+18

 

b) 5(6-y) =-5y+30

 

c) -7(2 z -3) =-14z+21

 

d) -8(-5-3 y) =24y+40

 

e) 6 ( 4x - 9) = 24x-54

 

f) -12(-5+3x) = -36x+60

 

2013-06-18T18:04:58+02:00

Il suffit d'appliquer la simple distributivité.

 

A = 3(x + 6)

A = 3x + 18

 

B = 5(6 - y)

B = 30 - 5y

B = -5y + 30

 

C = -7(2z - 3)

C = -14z + 21

 

D = -8(-5 - 3y)

D = 40 + 24y

D = 24y + 40

 

E = 6(4x - 9)

E = 24x - 54

 

F = -12(-5 + 3x)

F = 60 - 36x

F = -36x + 60